Antifungal effect of tissue conditioners containing poly(acryloyloxyethyltrimethyl ammonium chloride)-grafted chitosan on Candida albicans growth in vitro - Hsin-Lin Lee; Ren-Syue Wang; Yung-Chuang Hsu; Chuan-Chung Chuang; Hui-Rong Chan; Hsien-Chung Chiu; Yi-Bing Wang; Kuo-Yu Chen; Earl Fu (Elsevier, 2018)
Background/purpose: Denture stomatitis is a pathological condition affecting the mucosa underneath ill-fitting dentures, and Candida albicans is considered its main etiologic factor. Tissue conditioners are temporary lining materials often applied to dentures to treat inflamed tissues. However, tissue conditioners do not exert antifungal activity, and the soft surface texture harbors C. albicans easily. The aim of this study was to examine the antifungal activity of tissue conditioners modified with chitosan (CS) or a quaternized chitosan (QCS), which was synthesized by grafting 2-[(acryloyloxy)ethyl] trimethyl ammonium chloride onto CS. Materials and methods: Tissue conditioners containing varying weight percentages of CS or QCS were prepared as experimental discs 10 mm in diameter and 1 mm in thickness. Samples were co-cultured with C. albicans and the number of colony forming units was recorded. Other evaluations included cell toxicity and tensile bond strength to the resin denture base. Results: It was found significantly fewer fungal colonies in tissue conditioners modified with CS or QCS, and none when the weight percentage of QCS exceeded 5%. CS and QCS did not affect the viability of human gingival epithelium cells or fibroblasts, and tensile bond strength did not differ between control and modified tissue conditioners. Conclusion: This study provides a foundation for the development of QCS as a novel and safe antifungal agent applied to tissue conditioners in clinical practice.